Matters of violence : reflections on social and political violence in Sri Lanka - Uyangoda, Jayadeva; Biyanwila, Janaka; Social Scientists Association of Sri Lanka (Colombo : Social Scientists' Association, 1997)
Contributed essays.
Keywords: Violence -- Sri Lanka; Sri Lanka -- Social conditions